An Approach to the History of Latin American Philosophical Thought - Beorlegui, Carlos (Pensamiento. Revista de Investigación e Información Filosófica, 2016)
Latin American philosophical thought, mainly since the political emancipation of Latin America, has been persistently besieged by the question of its identity within the world philosophical scene, a question that in turn ineludes the questions of its legitimacy, authenticity and originality. If the universalist trend has persisted in following the parameters of European philosophy, the Americanist line has struggled to legitimize its intention to philosophize from and in relation to its specific socio-cultural circumstances. This work covers the history of Latin American philosophical thought from the point of view of this set of problems, following, above all, the americanist current.
Keywords: Identity; legitimacy; authenticity; originality; universalist; americanist; Latin American philosophy; positivism; liberation philosophy.